Support and emotional dependence in the story «La camisa de Margarita» - Godoy Suazo, Betsy Ariana (2020)
In this article I will address the relevance of emotional support in the story «La camisa de Margarita» by Ricardo Palma. To do this, I will begin by defining what is meant by emotional support. According to Blasco (n. d.) «emotional support [...] allows us to recognise our emotions in front of others. This support is based on displays of affection, empathy, active listening, acceptance, etc.» (para. 6). In the same way, I will deal with the emotional dependence that Palma shows us in this story, as he tells us of the sadness in which Margarita is immersed due to the fact that her father will not let her marry the man she loves. Two themes of great importance that continue to be reflected from those times to the current day.